FUNCTIONAL RESPONSE TO ENDOBRONCHIAL VALVE IMPLANTING TO THOSE SUFFERING FROM PULMONARY DESTRUCTIVE TUBERCULOSIS - L. A. Popova; E. A. Shergina; O. V. Lovacheva; T. R. Bagdasaryan; N. A. Chernykh; V. B. Nefedov (Туберкулез и болезни лёгких)
Goal of the study: to investigate the changes in ventilation and gas exchange function of the lungs before and after 1-1.5 months after installation of endobronchial valve (EV) aimed at cavity healing in pulmonary destructive tuberculosis patients.Materials and methods. 74 HIV negative patients in the age from 18 to 61 years old suffering from destructive pulmonary tuberculosis were examined. The changes in the pulmonary ventilation capacity (VC, FEV1 , FEV1 /VC%, PEF, MEF25,75) and blood gases (РаО2 , РаСО2, SaО2 %) before and in 4-6 weeks after EV installation have been studied.Results. After 1-1.5 months after EV installation no significant changes in the pulmonary ventilation function were found in 62.2% of patients, 43.2% of patients demonstrated no significant changes in gas exchange function and there were certain changes in the remaining patients. Reduction of pulmonary ventilation capacity due to large bronchi obstruction, restrictive changes and pulmonary gas exchange were manifested through reduction of FEV1 in 18.9% (95% CI 11.6-29.3%) of patients, PEF – in 20.3% (95% CI 12.7-30.8%), VC – in 22.9% (95% CI 14.9%-33.8%) and PaO2 – in 32.4% (95% CI 22.9-43.7%) of patients.Reduction of carbonic acid content in blood was observed in 27.0% (95% CI 18.3-38.1%) of patients. The improvement of gas exchange and ventilation function was the following: VC in 14.9% of patients (95% CI 8.5-24.7%), РаО2 – in 24.3% (95% CI 16.0-35.2%) and SаO2 – in 20.3% (95% CI 12.7-30.8%) of patients. Patients remained stable due to moderate intensity of changes.Frequency of negative and positive functional changes after installation of endobronchial valve for valve bronchial blocking (VBB) varies to some extent depending on the place of EV installation, volume of VBB and dissemination of tuberculous lesions.Lower installation of VBB versus upper one: VC increases more rarely (in 8.3 and 21.6% of patients, p < 0.05 respectively), FEV1 decreases more often (in 41.7 and 13.5% of patients p < 0.05 respectively), VC, PEF, РаО2 and SаO2 go down more often (p < 0.05).If tuberculous lesions are limited the cases when pulmonary ventilation capacity decreases after EV installation occur more often compared to disseminated tuberculous lesions and the cases when pulmonary ventilation capacity improves were observed only in case of the disseminated disease.